A Panopticon Revelation of the Power and Self-Discipline in Orwell’s 1984 - Baral, Rohit Prasad (Janapriya Journal of Interdisciplinary Studies, 2022)
The article aims to study and analyze Michel Foucault's concept of Panopticism and its implication in daily life and in literary texts. Panopticism is a concept where self-surveillance, distance surveillance and central control mechanisms are developed and implemented. Panopticism is the term used by Michel Foucault in which the surveillance, observations and monitoring systems are regulated in different ways and methods in different time periods. Panoptic surveillance of eighteenth century and the present systems of CC TV surveillance in Offices, Schools, Colleges and Banks is the mechanical representation of the panoptic concept. This panoptic observation creates power and controls people, create law and order, and also creates the dictatorial ruling over general people. This article follows the method of studying Jeremy Bentham and Mitchel Foucault's terms Panopticism and attempts to assimilate in the present concept of mechanics of distance surveillance through technology. It also applies the concept to study George Orwell's novel 1984. It concludes that the present concept of CC TV surveillance and others type of distance controlling systems resembles the idea as noted by Bentham, Foucault and applied by Orwell in the novel 1984. The issue of controlling people with Big Brother power in the novel is the panoptic observation and ruling over people by the rulers.